Detectable quorum signaling molecule via PANI-metal oxides nanocomposites sensors - Walaa S. Gado; Abdalrahman G. Al-Gamal; Mona Shaban E. M. Badawy; A. Labena; Khaled Zakaria; Khalid I. Kabel (Scientific Reports, 2024)
Abstract The detection of N-hexanoyl-l-homoserine lactone (C6-HSL), a crucial signal in Gram-negative bacterial communication, is essential for addressing microbiologically influenced corrosion (MIC) induced by sulfate-reducing bacteria (SRB) in oil and gas industries. Metal oxides (MOx) intercalated into conducting polymers (CPs) offer a promising sensing approach due to their effective detection of biological molecules such as C6-HSL. In this study, we synthesized and characterized two MOx/polyaniline-dodecyl benzene sulfonic acid (PANI-DBSA) nanocomposites, namely ZnO/PANI-DBSA and Fe2O3/PANI-DBSA. These nanocomposites were applied with 1% by-weight carbon paste over a carbon working electrode (WE) for qualitative and quantitative detection of C6-HSL through electrochemical analysis. The electrochemical impedance spectroscopy (EIS) confirmed the composites’ capability to monitor C6-HSL produced by SRB-biofilm, with detection limits of 624 ppm for ZnO/PANI-DBSA and 441 ppm for Fe2O3/PANI-DBSA. Furthermore, calorimetric measurements validated the presence of SRB-biofilm, supporting the EIS analysis. The utilization of these MOx/CP nanocomposites offers a practical approach for detecting C6-HSL and monitoring SRB-biofilm formation, aiding in MIC management in oil and gas wells. The ZnO/PANI-DBSA-based sensor exhibited higher sensitivity towards C6-HSL compared to Fe2O3/PANI-DBSA, indicating its potential for enhanced detection capabilities in this context. Stability tests revealed ZnO/PANI-DBSA's superior stability over Fe2O3/PANI-DBSA, with both sensors retaining approximately 85–90% of their initial current after 1 month, demonstrating remarkable reproducibility and durability.